Menciptakan Solidaritas dan Toleransi Masyarakat dalam Keberagamaan melalui Moderasi Beragama - Natanael Abraham (Jurnal Indonesia Studi Moderasi Beragama, 2024)
Pluralism is one of the most hotly debated themes today, especially among religious communities. Religious pluralism has a very sensitive potential to create conflict. The purpose of this study is to determine how much the level of tolerance interaction that exists in Jember Regency between religious communities and the impact of existing tolerance. The research method used descriptive qualitative. The data collection process uses three techniques, namely observation, interviews, and documentation. For data analysis techniques in this study, the author will use three streams of data acquisition, including (1) data reduction; (2) data display; (3) conclusion drawing/verification. The results of the research obtained the conclusion that the people of Jember Regency are united to create harmony and tolerance in religious life because according to them, they have in common as human beings. The contribution of this research is as a discourse and information for readers and academics related to the role of solidarity that fosters tolerance in religious life through religious moderation.